Phytotherapy for Dyspepsia by the Tribals of East Godavari District, Andhra Pradesh - . Seetharami Reddi, J. Suneetha, J. Koteswara Rao*; T.V.V (Journal of Phytology, 2011)
The paper presents a detailed account of the use of 33 taxa of 22 families as ethnomedicine for curing dyspepsia by the tribals of East Godavari district, Andhra Pradesh.